Effect of Ethanol Leaf Extract of Aspilia Africana on Activities of Some Serum Enzymes of Male Rats - Onyeulor , Chinasa J.; Umoh, Ezekiel U.; Eteng , Kenyoh K.; Obasi , Ifeanyi C.; Chikere-Njoku , Chiamaka N.; Ezeigwe , Donatus O. (American Journal of Biomedicine and Pharmacy, 2025)
The effect of ethanol leaf extracts of Aspilia africana (hemorrhage plant) on some serum enzyme activities on male albino Wistar rats were determined. A total of 48 male Wistar albino rats were used in this research, these were shared into 4 groups of 12 each. Group 1 was placed as the control, group 2 were given 500mg/kgBW of the extract, group 3 were given l000mg/kgBW of the extract and group 4 were given 2000mg/kgBW of the extract. The administration of the extract was done in batches (14 and 28days). Following the administration for the 14 days, batch 1 (which was gotten by selecting 6 rats randomly from each group) were sacrificed and the administration were continued with the remaining rats at the same doses for 28 days. Statistical analysis of serum enzyme activities for 14days showed that there was no significant difference in activities of ALT, AST and ALP of the treatment groups compared to the control. In 28 days, there were no significant difference in the activities of both alanine amino transferase and alkaline phosphatase among the groups, Aspartate aminotransferase concentration in the different experimental groups of the 28 days differed significantly from the control at p<0.05, showing potential toxicity to the heart tissue. Conclusively, that the ethanol leaf extract of Aspilia africana is safe and can be useful in the management hepatic conditions and other ailments due to it low toxicity.